Chapter Essays on the Spread of Humanistic and Renaissance Literary Civilization in the Slavic World (15th-17th Century). An Introduction - Siedina, Giovanna (Biblioteca di Studi Slavistici, 2020)
In this article the author, after briefly summarizing different interpretations of the Renaissance, shortly outlines some modes that have characterized the reception and study of Humanism and the Renaissance in Slavic countries. She then illustrates the content of the essays gathered in two recent histories of Ukrainian literature , with a special focus on the novelty of their interpretative approach. The author argues the importance of abandoning the old national-driven interpretation, in favor of the adoption of an areal and supranational point of view which allows the analysis of related cultural phenomena in a wider perspective.